FACTORS AFFECTING THE FUNCTIONAL STATUS OF PATIENT WITH MENINGIOMA IN DR. SAIFUL ANWAR GENERAL HOSPITAL MALANG - Dessika Rahmawati; Badrul Munir; Nanik Setijowati; Catur Ari Setianto; Ria Damayanti; Bimo Mubyarto (MNJ (Malang Neurology Journal), 2023)
Background: Meningioma is one of the most commonly reported primary central nervous system (CNS) tumors, originating from arachnoid meningeal cells and including intracranial extra-axial neoplasms. Although meningioma is considerably benign, the patient conditions are reported to be diverse resulting in severe and life-threatening neurological deficits. Hence the assessment regarding functional status is deemed pivotal to provide a prognostic perspective as patient presentation exhibits disability due to lesions and other factors. Objective: This research aims to analyze factors affecting the functional status of patients with meningioma in Dr. Saiful Anwar General Hospital Malang. Methods: An analytic retrospective study was conducted with cross-sectional study involving 62 samples from patients visits with meningioma brain tumor in RSUD dr. Saiful Anwar General Hospital Malang from January 2017 to December 2020. The data was selected through non-probability sampling, generating sampling type from brain tumor register data Neurology. Results: Data obtained from 62 meningioma patients in RSUD dr. Saiful Anwar General Hospital Malang met the inclusion criteria from January 2017 to December 2020, based on demographic characteristics such as age of <50 in 38 patients (61.3%) and age of >50 in 24 patients (38.7%). Clinically, it was found that 58 patients (93.5%) experienced headache, 28 patients (45.2%) experienced decreasing consciousness, 15 patients (24.2%) had hemiplegia, and 17 patients (27.4%) had hemiparesis, 17 people had hemiparesis. 17 patients (27.4%) experienced visual disturbances, and 24 patients (38.7%) are with seizures. Based on the radiology screening sites, 46 patients (74.2%) were screened in Convexity sphere, 9 patients (14.5%) were screened at Cranial base, 3 patients (4.8%) were screened at Parasagittal, and 4 patients (6.5%) were screene at Falx, from which the 41 patients (66.1%) exhibited herniation. Based on comorbidities, 12 patients (19.4%) had sepsis, and 1 patient (1.6%) had pneumonia. From the analysis test results, it was found that decreasing consciousness (GCS) was significantly correlated with functional status, referred to Karnofsky Performance Scale of <70 (p: 0.013, p <0.05). Seizures were reported to be correlated significantly with functional status, referred to Karnofsky Performance Scale of > 70 (p: 0.015, p<0.05). Tumor location was significantly correlated with functional status, reffered to Karnofsky Performance Scale of > 70 (p: 0.027, p<0.05). Conclusion: The factors affecting the functional status based on the Karnofsky Performance Scale (KPS) of a patient with meningioma at Dr. Saiful Anwar General Hospital Malang included: decreasing consciousness (GCS), and seizures, and tumor location.